L'île de Tatihou (Manche) à l'âge du Bronze Habitats et occupation du sol - Marcigny, Cyril; Ghesquière, Emmanuel (Documents d'archéologie française, 2003)
Tatihou, an island of the east coast of the Cotentin, recognised as a major natural, heritage and archaeological site, is being upgraded by the Manche county council. Since 1992, a maritime museum, a research centre and a seabird reserve have been established. It is against this background that preventive archaeology was undertaken from 1996 until 1998, and the highly exciting results are contained within this volume. Tatihou is now considered to be one of the major reference sites for the early and middle Bronze Age in the west of France, particularly because of the field organisation underscored by a network of ditches which criss-cross at right-angles.